Penerapan Algoritma C.45 Dalam Pengklasiﬁkasian Data Penjualan Gerai Makanan Cepat Saji Berbasis Website - Darmansah Darmansah; Willi Novrian; Tomy Nanda Putra; Budy Satria (Journal of Information System Research (JOSH), 2023)
With the development of technology, there are many methods that can be used to analyze various kinds of problems, both in the world of education, social and even the business world. One method that can be used is the data mining method. Fast food is one example of a business that is being built by many people today, especially in the city of Batam. With so many fast food outlets in the city of Batam, this study aims to classify the types of food that are in demand and not in demand in the city of Batam. To assist the writer in classifying the best-selling and not-selling food types, in this study the authors used the data mining method, namely applying the C.45 Algorithm approach. Apart from using the C.45 Algorithm to test the calculation results, the author uses a website-based information system. From the research that has been carried out, the results obtained are that the best-selling food for children is the Original Burger (BO) and for adults the best-selling type of food is Kebab (K), while the less popular type of food for all ages is Burger Crispy.